NUCLEAR KNOWLEDGE MANAGEMENT AND PRESERVATION: A CASE STUDY OF PAKISTAN - Khan, Shahid Riaz (The Nucleus, 2020)
The nuclear knowledge management (NKM) has become a major growing issue in the IAEA‟s Agenda. The use of nuclear technology in variety of application related to sustainable development, demands the preservation of nuclear knowledge. In developing countries the use of nuclear technology is much smaller compared to developed world. The nuclear knowledge management situation in the developing countries are not understood clearly. In case of Pakistan, the nuclear technology is being used in many areas of human need. These include energy, agricultural, medical and industrial applications. Also by the end of third decade, the authorities have set target to go for generating electricity through nuclear technology near to 800 MW. NKM is also vital for the new generation to understand the technology from elder‟s experiences and through proper knowledge preservation. This could only be done by adopting a proper nuclear knowledge management strategy.